Melalui Pendekatan Saintifik Model Pembelajaran Covid-19 Metode Blended Learning untuk Meningkatkan Hasil Belajar Peserta Didik Muatan Pembelajaran Bahasa Indonesia Tema Udara Bersih Bagi Kesehatan pada Kelas V SD Negeri 60 Payakumbuh Semester Ganjil Tahu - Noviarita Noviarita (Journal on Education, 2022)
The purpose of this study is to describe the use of the Covid-19 learning model with the blended learning method to improve student learning outcomes in Indonesian language learning content in class V at SDN 60 Payakumbuh. This type of research is Classroom Action Research. The research was carried out based on classroom action research steps with two cycles starting from the planning, implementation, observation and reflection stages. Research data in the form of test results, learning observations, field notes, and documentation of each learning improvement action. The source of research data is the process of learning activities. Data were obtained from the research subjects, namely teachers and students of class V, totaling 17 people, which was held from July to July. October 2021. The results of the research data analysis show that the use of the Covid-19 blended learning method can optimize student learning outcomes. This is evident from the increase in student learning outcomes in terms of knowledge and skills. The learning outcomes of the knowledge aspect have increased from 65.88 in the pre-cycle activities to 69.41 in the first cycle, increasing to 88.82 in the second cycle with an increase of 22.94. The learning outcomes of the skills aspect obtained an average of 67.64 in the pre-cycle, increasing to 81.76 in the first cycle and increasing again to 97.64 in the second cycle with an increase of 30.00. Based on the results of this study, the conclusions from research using the COVID-19 learning model in Indonesian language learning content need to be applied and developed in order improve the quality of education.